The Relationship between Character Traits and In Vivo Cerebral Serotonin Transporter Availability in Healthy Subjects: A High-Resolution PET Study with C-11 DASB - Jeong-Hee Kim; Hang-Keun Kim; Sang-Wha Lee; Young-Don Son; Jong-Hoon Kim (MDPI AG, 2023)
To elucidate the potential roles of serotonergic activity in human character traits (i.e., self-directedness, cooperativeness, and self-transcendence), we investigated the relationship between these character traits and serotonin transporter (5-HTT) in healthy subjects. Twenty-four participants underwent High-Resolution Research Tomograph-positron emission tomography scans with [11C]DASB. To quantify 5-HTT availability, binding potential (BPND) of [11C]DASB was obtained using the simplified reference tissue model. The Temperament and Character Inventory was used to assess subjects' levels of three character traits. There were no significant correlations between the three character traits. Self-directedness was significantly positively correlated with [11C]DASB BPND in the left hippocampus, left middle occipital gyrus, bilateral superior parietal gyrus, left inferior parietal gyrus, left middle temporal gyrus (MTG), and left inferior temporal gyrus (ITG). Cooperativeness was significantly negatively correlated with [11C]DASB BPND in the median raphe nucleus. Self-transcendence was significantly negatively correlated with [11C]DASB BPND in the right MTG and right ITG. Our results show significant correlations between the three character traits and 5-HTT availability in specific brain regions. In particular, self-directedness was significantly positively correlated with 5-HTT availability, suggesting that a goal-oriented, self-confident, and resourceful character may be related to higher serotonergic neurotransmission.